Sinergisitas Humas dan Jurnalistik sebagai Media Informasi pada Pemerintahan Provinsi Sumatera Utara : Studi Kasus Akun Instagram @Infosumutku - Ahmad Fadhlan; M Yoserizal Saragih (LPPM Institut Nasional Laa Roiba Bogor, 2024)
Today's social media, which consists of various platforms, has become the daily food for people from all walks of life. Parents, youth and children all have free access to social media. All circulating information can be reached with just one touch on smartphones and other electronic devices. Technological developments play a major role in the development of human civilization, especially in North Sumatra. Information that is educational to entertainment is very important to be accepted by the community. Since 2019 the Provincial Government of North Sumatra has no longer assigned the Public Relations Bureau to carry out public relations tasks, but has been assigned to the North Sumatra Communication and Information Service (Kominfo).Pemprovsu views social media Instagram @infosumutku as media that is very close to the community. In addition to the existence of this platform which is widely used by the public, Pemrovsu not only uses Instagram as a medium of information for the public, but also Twitter, Facebook, Tiktok, and the Website. North Sumatra Kominfo as an executor in the field of public relations at Pemprovsu has a strategy in carrying out its duties of disseminating information to the public. Not only that, North Sumatra Kominfo has many relationships with journalists and mainstream media which of course are embraced to become partners in disseminating information to meet the needs of the people of North Sumatra in particular. Keywords: Synergy, Public Relations, Journalism, Information Media